A study of consumer willingness to adopt two-dimensional anthropometric measurement systems - Liu, Lixian; Li, Yu; Li, Hao (Frontiers in Computer Science, 2025)
Online shopping has become common, but fitting clothes purchased online remains a challenge for both consumers and merchants. Two digital solutions are available: virtual fitting to try on clothes or using a 2D anthropometric measurement system to select the correct size. However, consumers’ experiences and perceptions of 2D measurement systems vary. To understand consumers’ willingness to adopt 2D anthropometric systems, this study reviewed the current use of these systems in China and abroad and created a model to identify the factors that influence adoption. The model was based on the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), with consumer perception as the mediator. Hypotheses were proposed based on this framework. A questionnaire survey was conducted to test these factors. A total of 410 valid responses were analyzed using SPSS to confirm the reliability and validity of the measurement dimensions. Then, structural equation modeling was used to test the hypotheses, and the results showed good model fit. Finally, path analysis and mediation tests revealed that consumer perceptions mediate the relationship between perceived usefulness, perceived ease of use, and adoption attitudes. These findings highlight the importance of these factors in predicting consumer adoption of new systems. Fashion managers and designers should adjust marketing strategies and technology development based on factors like perceived usefulness, ease of use, and consumer perceptions (e.g., enjoyment, value, and risk) to encourage adoption.